AIT :
Bound with: A.I.T. Bulletin intérieur ... (ZK 30080). - Continued by: Informacion A.I.T. (ZF 60860). - See also: A.I.T. Bulletin d'information ... (ZK 30080), A.I.T. Organe de l'Association ... (ZF 30029), A.I.T. Organo de la Asociacion ... (ZF 30029).